Angiolymphoid hyperplasia with eosinophilia responded well to dupilumab in two cases - Yi Jiang; Yu Xiao; Yang Wang; Panpan Shang (Journal of Dermatological Treatment)
Purpose Angiolymphoid hyperplasia with eosinophilia (ALHE) is a rare, benign vasoproliferative skin disorder. The overall efficacy of current treatments remains suboptimal with frequent recurrence. Recent studies have suggested the type-2 inflammation features of ALHE and emphasized the role of T cells, which calls for further validation.Material and methods We describe two patients with ALHE, a 65-year-old man and a 27-year-old woman, treated with dupilumab, an IL-4 receptor α-antagonist that has been widely used in chronic skin diseases associated with type 2 inflammation.Results Both patients achieved sustained responses to dupilumab with favorable safety profiles. The 65-year-old man showed significant improvement after 2 months of treatment, and discontinued treatment after 12 cycles. No relapse was observed during a 3-month follow-up. The 27-year-old woman showed reduced nodules on the forehead after 4 cycles of treatment and continued the treatment at 300 mg per month for 7 months without relapse.Conclusions These cases support the type 2 inflammation features of ALHE and underscore the critical role of T cells in the pathogenesis. Moreover, these cases also highlight the promising use of dupilumab or other T-helper cell type 2-mediating therapies in treating ALHE.